Performance Investigation of Software Agents in Artificial Intelligence and Document Object Model Domain - Abhijit Bora; Tulshi Bezboruah (IAES Indonesian Section, 2023)
Assessing the performance impact of Artificial Intelligence on questionnaires of pharmacological unit is necessary from the perspective of medical practitioners as well as patient’s perspectives. The proposed study ascertained that software agents based on Artificial Intelligence and Document Object Model domain can deliver better service in medical units in contrast to its other deployment methodologies. So, the proposed work, a prototype is developed by using dialog control class file which accesses the system resources through the kernel objects. We call the software agent as MBot (prototype bot for medical unit). The prototype is deployed for pharmacological unit where the clinical instruction against the disease can be suggested. The experimental arrangement, deployment architecture of MBot, performance metrics and the statistical analysis for the observed data sample are discussed here. The novelty of the proposed work highlights the performance aspects of MBot against its counterpart. It reveals that better response time and validates that the dialog controller class of MBot can process questionnaires through its intelligence.